2008
DOI: 10.1111/j.1468-3083.2008.02888.x
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of melanoma in patients with atopic dermatitis

Abstract: A low risk to develop melanoma was found in AD patients. However, the results must be interpreted with caution since the small number of expected cases of melanoma makes the risk estimate sensitive to chance effects. We hypothesize that formation of naevi and progression to melanoma is counteracted by the inflammatory process in the skin of AD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
2
21
1
1
Order By: Relevance
“…A very recent Danish cohort study [ 9 ], on more than 30,000 AD patients, also showed results in the same direction. [ 10 ], which was not the case in our cohort [ 6 ].…”
Section: Epidemiological Studiescontrasting
confidence: 67%
“…A very recent Danish cohort study [ 9 ], on more than 30,000 AD patients, also showed results in the same direction. [ 10 ], which was not the case in our cohort [ 6 ].…”
Section: Epidemiological Studiescontrasting
confidence: 67%
“…An association between cancer and allergy has been previously recognized [34]. The incidences of glioma, colorectal, larynx, esophageal, oral, pancreatic, stomach, and uterine cancers, as well as melanoma and non-Hodgkin's lymphoma, were found to be decreased in the allergic condition, whereas the incidences of bladder cancer, lymphoma, and myeloma, and prostate cancer were increased in the allergic condition [35], [36]. Case-control studies, multicenter case-control studies, and rigorous meta-analyses have provided stronger support for the relationship between allergy and cancer development [37], [38], [39], [40].…”
Section: Discussionmentioning
confidence: 91%
“…Such alterations are likely to influence the risk of skin tumors. For instance, in psoriasis 12 and atopic dermatitis 13 it has been shown that subjects affected by these diseases have a reduced number of melanocytic nevi, suggesting that cytokine networks involved in such conditions might inhibit melanogenesis, melanocyte growth, and/or progression to nevi.…”
Section: Methodsmentioning
confidence: 99%